Application of The Dispute Referred for A Preliminary Ruling in Handling Criminal Cases Which Contains Civil Elements by Police Investigators - I Kadek Patra; H.Nurianti RS; I Made Mulyawan Suabawa (Jurnal Syntax Transformation, 2025)
The application of Prejudice Geschill, or prejudicial disputes, in criminal cases with civil elements in Indonesia remains a significant legal challenge. This concept allows the suspension of criminal cases when civil disputes must be resolved first, yet the Indonesian legal framework provides insufficient guidance on how investigators should manage such cases. This research examines the application of Prejudice Geschill during criminal investigations involving civil issues and explores the legal gaps in existing regulations, particularly Perma No. 1 of 1956 and SEMA No. 4 of 1980. The study uses an empirical juridical research approach, combining a statute approach, conceptual approach, and case study method to analyze Police Report Number: LP/B/15/III/2024/SPKT/POLRES GIANYAR as a case study. The findings reveal that while the law allows the suspension of investigations, the lack of clear procedural guidelines causes inefficiencies, leading to delays in both criminal and civil proceedings. The study suggests reforming the legal framework to provide more precise guidelines for investigators and the judiciary in handling cases with civil elements. Legal reforms could streamline investigations, reduce delays, and ensure more effective legal outcomes.